2012
DOI: 10.1177/1934578x1200700320
|View full text |Cite
|
Sign up to set email alerts
|

Host-Guest Chemistry of Alkaloids

Abstract: Binding of alkaloids by different hosts (native and modified cyclodextrins, cucurbiturils, calixarenes, and metal complexes of porphyrin and Salphen-type ligands), as well as receptor properties of alkaloid based hosts are reviewed. With alkaloids as guests, the largest binding constants and most significant spectral changes, in particular strong fluorescence enhancements induced by complexation with isoquinoline alkaloids, are observed with cucurbituril hosts. Cyclodextrins are successfully employed for impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Isoquinolines refer to a class of fluorophores that are derived from the parent heterocyclic isoquinoline scaffold (Figure ). Although isoquinoline itself is not fluorescent, many of its derivatives are highly fluorescent, with absorption and emission maxima tunable throughout the visible region. , Additional tuning of the photophysical properties of isoquinoline derivatives can come from inclusion of the fluorophore in a supramolecular host, which provides steric protection from degradation and leads to enhanced quantum yields. Many isoquinoline derivatives are commercially available, and others can be synthesized via straightforward synthetic procedures . Isoquinoline-derived turn-on fluorescent sensors have been used for the detection of a variety of cations and anions, although concerns about the toxicity of isoquinoline derivatives have been noted …”
Section: Common Fluorophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoquinolines refer to a class of fluorophores that are derived from the parent heterocyclic isoquinoline scaffold (Figure ). Although isoquinoline itself is not fluorescent, many of its derivatives are highly fluorescent, with absorption and emission maxima tunable throughout the visible region. , Additional tuning of the photophysical properties of isoquinoline derivatives can come from inclusion of the fluorophore in a supramolecular host, which provides steric protection from degradation and leads to enhanced quantum yields. Many isoquinoline derivatives are commercially available, and others can be synthesized via straightforward synthetic procedures . Isoquinoline-derived turn-on fluorescent sensors have been used for the detection of a variety of cations and anions, although concerns about the toxicity of isoquinoline derivatives have been noted …”
Section: Common Fluorophoresmentioning
confidence: 99%
“…Although isoquinoline itself is not fluorescent, many of its derivatives are highly fluorescent, 603 with absorption and emission maxima tunable throughout the visible region. 427,604 Additional tuning of the photophysical properties of isoquino- line derivatives can come from inclusion of the fluorophore in a supramolecular host, 605 which provides steric protection from degradation and leads to enhanced quantum yields. 606−608 Many isoquinoline derivatives are commercially available, and others can be synthesized via straightforward synthetic procedures.…”
Section: Isoquinolinesmentioning
confidence: 99%
“…Host–guest chemistry, which frequently involves the formation of outer-sphere complexes, has applicability in stabilization of reactive intermediates, sensing of chemical species and modeling of biological systems, among others. As such, it has been the target of an increasing number of studies in recent years. Hydrogen bonding is an important type of interaction supporting the formation of outer-sphere complexes, as are anion-π interactions, first described in this context by Demeshko et al and de Hoog et al The latter support spatial interactions in biological systems and the assembly of supramolecular structures, and have gained increasing attention in catalysis. Known examples involve electron deficient aromatics such as N-heterocycles, fluoroarenes or trinitrobenzene interacting with mono and polyanions. Interactions leading to outer-sphere complexes of lanthanide [Ln III ] ions have been studied due to the importance of these ions in magnetic resonance imaging, shift reagents and as structural probes in enzymes and biomolecules in general. , Further, outer-sphere interactions also play an important role in the actinide/lanthanide separation in nuclear reprocessing. However, examples where the Ln III -bearing species is completely enveloped by a ligand moiety are extremely rare, since in the presence of other coordinating ligands the counterions or water molecules of hydration dissociate and the ligands, such as N-heterocycles, bind through their heteroatoms. Nonetheless, Wang et al recently reported the formation of a tetragonal prismatic complex in which [Ln­(H 2 O) 8 ] 3+ is enclosed in a [Ln 2 L 4 (H 2 O) 2 ] + cage; L is 4-amino-1,2,4-triazole-bridged 3,3′-biphenylcarboxylato. The carboxylato groups coordinate two Ln III ions, forming the capsule, and the amine moiety hydrogen-bonds the cationic guest.…”
Section: Introductionmentioning
confidence: 99%
“…SCXn can encapsulate alkaloids of pharmaceutical interest (Megyesi & Biczók, 2006Yatsimirsky, 2012). Previous results demonstrated that these cavitands are capable of binding as many coralyne (Cor) molecules as the number of their 4-hydroxybenzenesulfonate units and the largest association efficiency is reached with SCX8 (Megyesi & Biczók, 2010).…”
Section: Drug Loading In the Nanoparticlesmentioning
confidence: 99%